Kajian Kinerja Bagian Jalinan (Studi Kasus : Jl. Niaga 1 – Jl. Yos Sudarso, Kota Tarakan) - Iif Ahmad Syarif; Noerman Adi Prasetya; Rahmad Aidil; Rahmat Faizal; Edy Utomo; Ahmad Hernadi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2017)
This study aims to determine the performance on a single weave that occurred on Jl.Niaga I - Jl. Yos Sudarso, Tarakan City. The performance is capacity, degree of saturation, speed, and travel time. With these performance parameters serve as based of planning in transportation infrastructure. The results of this study are also expected to provide recommendations to users, planners and policy makers in an effort to solve traffic problems, especially to reduce the delay that occurs in a single wave that occurred on Jl Niaga I-Jl. Yos Sudarso Kota Tarakan.